2022
DOI: 10.1177/15589447211066346
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inflammatory Markers and Amputations in Hand Osteomyelitis: A Retrospective Review of 146 Cases

Abstract: Background: The diagnosis of hand osteomyelitis requires correlation of clinical, radiological, and microbiological findings. The role of serum inflammatory markers in diagnosing and prognosticating hand osteomyelitis remains uncertain. We sought to determine the utility of inflammatory markers in the diagnosis and follow-up of hand osteomyelitis, and their ability to predict outcomes, particularly amputation. Methods: We retrospectively reviewed 146 patients diagnosed with hand osteomyelitis and with serum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In a study on hand osteomyelitis, Wyman et al found C-reactive protein(CRP) to be the most sensitive marker and a CRP value greater than 100 mg/L was found strongly associated with sepsis. Total leucocyte count, NLR and also PLR were found to be of limited usefulness in this series [45].…”
Section: Discussionmentioning
confidence: 60%
“…In a study on hand osteomyelitis, Wyman et al found C-reactive protein(CRP) to be the most sensitive marker and a CRP value greater than 100 mg/L was found strongly associated with sepsis. Total leucocyte count, NLR and also PLR were found to be of limited usefulness in this series [45].…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies had addressed the role of NLR, MLR, and PLR in infections and characterized the clinical prediction potential for bacterial infection and nonspecific infection [ 10 14 ]. In terms of research related to bone infections, these immune-related biomarkers, such as WBCs, CRP, ESR, NLR, MLR, and PLR, are increasingly being evaluated for their abilities of fast and early diagnosis of osteomyelitis and to predict complications [ 26 28 , 36 38 ]. In diabetic foot infection patients, PLR was significantly higher in osteomyelitis, and the cut-off value PLR > 187.3 had a sensitivity of 67.9% and a specificity of 59.1% in predicting osteomyelitis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative NLR may help to recognize postoperative delirium in elderly patients undergoing surgery for lower limb fracture under nongeneral anaesthesia [ 25 ]. On the other hand, the predictive value of these markers for the prognosis of hand osteomyelitis, surgical site infection after spinal instrumentation surgery, and periprosthetic joint infection following total hip arthroplasty also needs to be further studied [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study also highlights the potential challenges in establishing the diagnosis of hand OM in SRP. Clinicians cannot always rely upon elevated inflammatory markers (ie, CRP), 8 and established radiographic abnormalities may not be present at baseline. Our study also benchmarks the high morbidity and poor outcome, including the potential need for partial digital amputation, from hand OM in SRP.…”
Section: Discussionmentioning
confidence: 99%
“…The median (interquartile range [IQR]) age of patients was 61 (8) years, and with 4 males (57%) and 3 females (43%), these proportions were comparable to a larger cohort of hand OM patients. 7 Most (n = 6) of the patients had connective tissue diseaseassociated RP with the majority within the SSc spectrum of disorders (n = 5) and 1 patient with polymyositis, with a range of ANA patterns: anticentromere (n = 2, 29%), fine speckled (n = 1, 14%), coarse speckled (n = 1, 14%), and a speckled and nucleolar pattern (n = 1, 14%). Extractable nuclear antigen was positive in 3 patients (43%), including 1 patient with RNA polymerase III positive.…”
Section: Case Seriesmentioning
confidence: 99%